An investigation on antibacterial filler property of silver nanoparticles generated from Walnut shell powder by insitu process. (2021) - Mohan, S.; Panneerselvam, K.
Abstract: Walnut Shell Powder (WNSP) was immersed in 5 (milli Molar) mM Silver Nitrate solution. The solutions were maintained at 80 0 C for a day to ensure in-situ generation of silver nanoparticles with the aid of the one step hydrothermal method. The modified WNSP had spherical AgNPs with an average size of 85 nm. FTIR showed some structural variations in both the unchanged and changed WNSP. X-ray diffraction (XRD) results confirmed the formation of in-situ generation of silver nanoparticles in the modified WNSP. Antibacterial studies have showed that there are no inhibition zones formed on WNSP. But in modified WNSP shown the excellent inhibition against both gram negative and gram positive bacteria's. The zone of inhibition formed against bacteria ranging from 11 mm to 18 mm in diameter. Hence, modified WNSP acts as a low cost filler when making polymer composites for medical and food packing applications.